Non-nutritive sweetener regulation and health: analysing applications to vary Australian and New Zealand food standards. (25th February 2023) - Russell, Cherie; Baker, Phillip; Grimes, Carley; Lawrence, Mark A
Summary: We aimed to understand the process of setting or varying food standards related to non-nutritive sweeteners (NNS) in Australia and New Zealand. Overconsumption of added sugars is a risk factor for non-communicable diseases. Limiting added sugar consumption is recommended by the World Health Organization. NNS are sweet substances with little to no energy that can be used to maintain the sweetness of packaged food when added sugar is reduced. The health and dietary pattern impacts of NNS are contested. Understanding how and why applications for NNS are submitted, assessed and approved within food regulatory systems is important to contextualize the increasing availability of NNS in the food supply. We completed an interpretive content analysis of applications to change the Food Standards Australia and New Zealand (FSANZ) Code, risk assessments and stakeholder submissions. Literature used in risk assessments were drawn from a mixture of documents supplied by industry and peer-reviewed studies. Risk assessments were primarily focussed on toxicological outcomes, while broader public health outcomes were not explicitly considered. Consumption data available to FSANZ were collected several years prior to dietary exposure assessments, and thus may not accurately represent current intakes. The study findings raise questions about whether the scope of what constitutes a 'risk' to public health in the setting of food standards needs to extend beyond immediate toxicological and food safety concerns, to include longer-term dietary balance considerations.